FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN KELUARGA MISKIN DI KECAMATAN MANDOR KABUPATEN LANDAK - B01112060, ELA CHRISTIN ARGANATA (Jurnal Pembangunan dan Pemerataan, 2016)
This study aims to examine and analyze factors that influence the income of poorfamily in Mandor District of Landak Regency. This research uses uatitative-descriptivemethod to analyze cross section data. Data were collected by questionnaire, interview anddocumentry. Multiple linear regression analysis and Eviews 8 data processed the data. Thesampel of population was 63 heads of the family.The findings show that education (level of significance : 0,0265 < 0,05), working hours(level of significance : 0,0009 < 0,05) and the numbers of family member (level ofsignificance : 0,0000 < 0,05) are variables the have positive and significant inluence to theincome of poor family. However, Age variable contributes negative and insignificant effect tothe income with the level significance 0,3636 > 0,05.Key word : education, age, working hours, the number of family member.